2009
DOI: 10.1111/j.1365-2516.2009.02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in factor VII gene modifies phenotype of severe haemophilia

Abstract: The basis for 10-15% of patients with severe haemophilia having clinically mild disease is not fully understood. We hypothesized that polymorphisms in various coagulant factors may affect frequency of bleeding while functionally significant polymorphisms in inflammatory and immunoregulatory genes may also contribute to variations in the extent of joint damage. These variables were studied in patients with severe haemophilia, who were categorized as 'mild' (<5 bleeds in the preceding year, <10 World Federation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
(43 reference statements)
0
29
0
1
Order By: Relevance
“…6,9,12 This is partially explained by the youngest patients in our study still being only 2.4 years of age. A few of these patients have not, as yet, had a joint bleed, and when they do, if the analysis were to be redone, the median age at first joint bleed would likely be slightly higher.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…6,9,12 This is partially explained by the youngest patients in our study still being only 2.4 years of age. A few of these patients have not, as yet, had a joint bleed, and when they do, if the analysis were to be redone, the median age at first joint bleed would likely be slightly higher.…”
Section: Discussionmentioning
confidence: 70%
“…Several retrospective studies have looked at the effect of coinheritance of prothrombotic mutations, with contradictory results. 6,9,[14][15][16][17][18][19][20][21][22][23][24][25] Some studies have found that severe hemophiliacs carrying a prothrombotic mutation have a milder phenotype characterized by older age at diagnosis, 25 older age at first bleed, 15,17,26 lower annual bleeding frequency, and less arthropathy. 21,22 In contrast, other studies failed to find significant differences in severity of disease attributable to the presence of a prothrombotic mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients with von Willebrand disease, 1.5% were found to harbor multiple coagulopathies requiring different treatment strategies (Asatiani and Kessler 2007); secondary sites included at least seven different genes among these patients. Apparently, variations in the factor VII ( F7 ) gene can ameliorate the phenotype in severe hemophilia (A/B) resulting in a milder phenotype (Jayandharan et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Haemophilia A (HA) and haemophilia B (HB) are X-linked bleeding disorders caused by a deficiency or dysfunction of coagulation factor VIII and FIX respectively [1]. Heterogeneous mutations in either the F8 or F9 gene, including a variety of inversions, insertions, deletions and point mutations have been reported to contribute to the bleeding phenotype in patients [2][3][4]. The identification of such disease-causing mutations is important for the precise genetic diagnosis of this condition in families affected with haemophilia [1].…”
mentioning
confidence: 99%